From social media use to FOMO: The moderating power of self-control among Gen Z blind box buyers - Joselyn Tiofanny; Fransisca Iriani Roesmala Dewi; Willy Tasdin (Priviet Social Sciences Journal, 2026)
This study aimed to examine the role of self-control as a moderating variable in the relationship between social media use and Fear of Missing Out (FOMO) among Generation Z individuals who purchase blind boxes in the Greater Jakarta Area (Jabodetabek). The background of this research is rooted in the rising consumption trend of blind boxes, which is influenced by digital media and potentially reinforces the tendency toward FOMO. This study employed a quantitative approach with a correlational predictive design. The research participants consisted of 117 Generation Z individuals residing in Jabodetabek who used social media for at least one hour per day and had purchased blind boxes within the last year. Data were collected using the Social Media Use Integration Scale (SMUIS) by Jenkins-Guarnieri et al. (2013) (α=0.840), the FOMO Scale by Zhang et al. (2020) (α=0.977), and the Brief Self-Control Scale (BSCS) by Ferrari et al. (2009) (α=0.967). The data were analyzed using Moderated Regression Analysis (MRA). The results indicate that self-control moderates the relationship between social media use and FOMO (p=0.017; ∆R²=0.010), where individuals with low self-control tend to experience higher FOMO. These findings affirm the importance of self-control in helping Generation Z adaptively manage digital social pressures in the social media era.